Given Step 1 Step 2 8(3x – 7) = -6(x + 7) + 4 24 x – 56 = -6x – 42 + 4 24 x – 56 = -6x + 46 30 x = 102

Question

Given
Step 1
Step 2
8(3x – 7) = -6(x + 7) + 4
24 x – 56 = -6x – 42 + 4
24 x – 56 = -6x + 46
30 x = 102
17
X =
5
Step 3 the
Step 4

in progress 0
Doris 5 months 2021-09-05T08:46:33+00:00 1 Answers 0 views 0

Answers ( )

    0
    2021-09-05T08:47:58+00:00

    Answer:

    fc;iuESDGKXCBNpqieyfhzxcbjm n

    Step-by-step explanation:

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )